2006
DOI: 10.1111/j.1440-0960.2006.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in psoriasis improves after standardized administration of narrowband UVB phototherapy

Abstract: SUMMARY Psoriasis is a chronic fluctuating dermatosis with demonstrable impact on patients' quality of life. Our aim was to investigate if narrowband UVB phototherapy administered to psoriatic patients in a standardized manner leads to an improvement in patients' perceived quality of life. A total of 138 patients with psoriasis were recruited from referrals to the Skin and Cancer Foundation, Australia between January 1998 and September 2002. Patients had psoriasis inadequately controlled by topical therapies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…6 Baseline DLQI scores are indicative of moderate QoL impairments associated with the disease, similar to those reported by other researchers. 5,16,[19][20][21] Phototherapy led to a significant decrease of DLQI score for 'symptoms and feelings' and 'treatment' subgroup that corresponds to results reported by other authors. 21 The QoL affection in the 'treatment' domain is expected since psoriasis is a chronic course skin disease that requires long-term management.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…6 Baseline DLQI scores are indicative of moderate QoL impairments associated with the disease, similar to those reported by other researchers. 5,16,[19][20][21] Phototherapy led to a significant decrease of DLQI score for 'symptoms and feelings' and 'treatment' subgroup that corresponds to results reported by other authors. 21 The QoL affection in the 'treatment' domain is expected since psoriasis is a chronic course skin disease that requires long-term management.…”
Section: Discussionsupporting
confidence: 88%
“…The significant positive changes in the quality of life observed in psoriasis (pain, burning, itching) and emotions (disturbance and anxiety) observed by us have been reported by other authors as well. 16,21 In other areas, such as 'daily activities' , 'work and school' , and 'personal relationships' the changes were statistically not significant.…”
Section: Discussionmentioning
confidence: 95%
“…20 Clinical trials use now both tools. Main treatments report impact on physicians and patient-related outcomes [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] but biologics have been extensively studied on the latest aspect. [23][24][25][26][27][28]30,32,34,39 Despite these recent successes we must be modest.…”
Section: What Is Living With Treatments Of Psoriasis?mentioning
confidence: 99%
“…Fifty-eight papers were obtained for full paper review, of which 35 papers were identified as eligible for inclusion into the review. Reasons for exclusion included study design was experimental[28-43], sample size too small[44], the patients included were originally from a clinical trial[3,45-51], the study involved retrospective identification of patients[14,15,52-54] and the study was just a description of medications used with no attempt to assess outcomes[55]. …”
Section: Resultsmentioning
confidence: 99%
“…Third, the cut-off of 100 patients to define large scale may have meant other important observational studies were excluded. However, only one study was excluded on the basis of sample size [44]. …”
Section: Discussionmentioning
confidence: 99%